PENGARUH RASIO MEDIA, RESIRKULASI DAN UMUR LUMPUR PADA REAKTOR HIBRID AEROBIK DALAM PENGOLAHAN LIMBAH ORGANIK - Muhammad Irfa'i (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
The research was aimed to obtain optimized performance of aerobic hybrid reactor. This research was performed in laboratory-scale. In order to obtain an optimal reduction of organic content, variations of media ratio (0%, 15%, 30% and 45%), recirculation ratio (0%, 25%, 50% and 75%) and sludge age (10 days and 20 days) were made. The result showed that media ratio, resirculation ratio and sludge age gave significant effect to organic removal. The Chemical Oxygen Demand (COD) removal rate was 78,19% which occurred at 30% media ratio, 75% recirculation ratio and sludge age of 20 day.